Standard non-target tests for risk assessment of plant protection products are unsuitable for entomopathogenic fungi—a proposal for a new protocol - Lara Reinbacher; Sven Bacher; Eva Praprotnik; Giselher Grabenweger (Journal of Soils and Sediments, 2021)
Purpose The successful implementation of a plant protection product depends on its effectiveness against a target species and its safety for the environment. Risk assessment schemes have therefore been devised to facilitate classification and regulation. These guidelines, however, are directed towards chemical substances and are in many cases less suitable for the assessment of products employing microorganisms. Methods In this study, we developed a protocol for non-target testing of soil-applied entomopathogenic fungi for the biocontrol of insect pests. Using the predatory mite Gaeolaelaps ( Hypoaspis ) aculeifer as a non-target model organism, our protocol evaluates the lethal and sublethal effects of the fungus in recommended and ten-fold field concentrations. Results The proposed protocol considers fungal biology when setting test duration, endpoints, and quality control measures. To assess its practicability, we performed a trial with Metarhizium brunneum ART2825 as a representative entomopathogenic fungus. The biocontrol agent was able to infect a susceptible host and reproduce, showing that potential hazards can be detected using our approach. No hazard was detected for the non-target species, with no statistically significant differences in 5-week survival and reproductive output between treated and untreated groups. Conclusion Based on our results, the protocol is deemed appropriate for the detection of non-target effects. Subject to further validation, our approach could thus provide the basis for standardized protocols for the evaluation of the environmental safety of biocontrol organisms.